2019
DOI: 10.31699/ijcpe.2019.2.7
|View full text |Cite
|
Sign up to set email alerts
|

New Study of Mgo Nps in Drilling Fluid to Reduce Stick-Slip Vibration in Drilling System

Abstract: Stick-slip is kind of vibration which associated with drilling operation in around the bottom hole assembly (BHA) due to the small clearance between drill string & the open hole and due to the eccentric rotating of string. This research presents results of specific experimental study that was run by using two types of drilling mud (Fresh water Bentonite & Polymer), with/without Nanoparticle size materials of MgO in various ratios and computes the rheological properties of mud for each concentration [Yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Cai et al (2012) found that adding unmodified nanosilica into WBMs could significantly reduce the invasion of water into the shale. Some research studied the effect of other inorganic nanoparticles on the wellbore stabilizing performance of drilling fluid such as nano grapheme (Taha and Lee, 2015), nano TiO 2 (Cheraghian et al, 2014), and nano MgO (Alssafar and Al-Mahdawi, 2019). Nano polymers (Xu et al, 2017(Xu et al, , 2018Zhang et al, 2018) having good flexibility could plug irregular shale pores by transformation and have strong interaction with shale matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al (2012) found that adding unmodified nanosilica into WBMs could significantly reduce the invasion of water into the shale. Some research studied the effect of other inorganic nanoparticles on the wellbore stabilizing performance of drilling fluid such as nano grapheme (Taha and Lee, 2015), nano TiO 2 (Cheraghian et al, 2014), and nano MgO (Alssafar and Al-Mahdawi, 2019). Nano polymers (Xu et al, 2017(Xu et al, , 2018Zhang et al, 2018) having good flexibility could plug irregular shale pores by transformation and have strong interaction with shale matrix.…”
Section: Introductionmentioning
confidence: 99%